Hypertriglyceridemia as an independent predictor of adverse prognosis in female patients with acute myocardial infarction: a comprehensive retrospective cohort study - Ma, Shan; Hu, Yanqing; Zhu, Yuanting; Liu, Shuaiye; Wu, Yang (Frontiers in Nutrition, 2025)
BackgroundAcute myocardial infarction (AMI) has notable sex-specific differences in clinical outcomes. While low-density lipoprotein cholesterol (LDL-C) is a longstanding core for atherosclerotic cardiovascular disease (ASCVD) risk assessment, the prognostic value of hypertriglyceridemia (HTG) in AMI patients—especially its sex-specific impact—remains unclear. This gap is critical as HTG is more common in women but understudied in post-AMI populations.MethodsA retrospective cohort included 850 consecutive AMI patients (412 females, 438 males) admitted to the Seventh Affiliated Hospital of Sun Yat-sen University (Jan 2019–Dec 2024), stratified by HTG (triglycerides ≥2.2 mmol/L). Median follow-up was 2.6 years, with outcomes: all-cause death, heart failure, major adverse cardiovascular events (MACE). Confounding was controlled via multivariate Cox regression, E-value calculation, and 1:1 propensity score matching. HTG’s predictive value was assessed via receiver operating characteristic (ROC) curves; post hoc power analysis confirmed ≥80% power (α = 0.05) for female all-cause death associations.ResultsHTG prevalence was 35.1% overall (females 54.4% vs. males 31.1%). HTG patients had higher all-cause death (18.8% vs. 4.7%), heart failure (20.8% vs. 5.3%), and MACE (21.8% vs. 5.4%). Female HTG patients had the highest event rates (all-cause death 28.4%, heart failure 30.2%, MACE 31.5%), while males with HTG only had higher MACE (11.0% vs. 5.3%). HTG independently predicted all outcomes in females (death HR = 3.89, heart failure HR = 4.21, MACE HR = 4.35) but only weakly associated with male MACE (HR = 2.05). E-value (4.2 for female death) and matching (284 patients, female death HR = 3.62) validated robustness. Adding HTG improved death prediction (ROC AUC 0.78 vs. 0.73) with net reclassification improvement 0.23.ConclusionHTG is a strong independent predictor of adverse AMI outcomes, with a far stronger effect in females. Routine triglyceride screening and targeted therapies (e.g., fibrates, icosapent ethyl) are needed for female AMI patients.